Distribution and expression of chicken endogenous retroviruses in the host genome - Borisenko, L.G.; Rynditch, A.V.; Bernardi, G. (Біополімери і клітина, 2004)
The distribution of seven groups of endogenous retroviruses (ALV-related ev loci, HERV-I-related proviruses, EAV-HP, EAV-0, E-33, E-51, ART-CH) in the genome of domestic chicken (Gallus gallus) was studied according to the composition (long-range variation of GC-content) of the host genome. GC-rich proviruses (ev loci, ART-CH and EAV-0) have been localized mainly in GC-richest isochore families H2, H3 and H4, GC-poor HERV-I-related proviruses, E-51 and E-33 localized in GC-poor isochore families L1, L2 and also in H1 (isopycnicity). GC-rich EAV-HP, except expected distribution GC-rich isochores, present also in GC-poor compartments. Investigation of expression by RT-PCR and analysis of EST databases provided a tissue-specific patterns that could change the picture of proviral distribution due to reintegration. Reasons of endogenous retrovirus isopycnicity are likely to be the compositional match between the integrant and the chromosomal region of the host, that led to the stability of integration. Розподіл семи груп ендогенних ретровірусів (ALV-родинні, HERV-I-родинні, EAV-HP, EAV-0, E-33, E-51, ART-CH) у геномі курки досліджували у зв'язку з композиційним складом (варіюванням GC-вмісту) геному хазяїна, GC-багаті pempoвіруси (ALV-родинні, ART-CH ma EAV-0) локалізовані, головним чином, в GC-найбагатших родинах ізохор Н2, НЗ і Н4, GC-бідні HERV-1-родинні провіруси, Е-51 та Е-33 локалізовані в GC-бідних родинах ізохор LJ, L2, а також в НІ (ізопікнічність). GC-багатий ретровірус EAV-HP, окрім очікуваної наявності в GC-багатих ізохорах, присутній також в GC-бідних ком пар тментах. Дослідження експресії шляхом RTPCR, а також аналіз баз даних EST свідчать, що експресія ендогенних ретровірусів курки може бути тканиноспецифічною. Це, в свою чергу, може впливати на картину провірусної локалізації внаслідок реінтеграції. Причиною ізопікнічної локалізації ендогенних ретровірусів є композиційна відповідність між інтегрованою послідовністю та хромосомною ділянкою хазяїна, що забезпечує стабільність інтеграції. Распределение семи групп эндогенных ретровирусов (ALV-родственные, HERV-I-родственные, EAV-HP, EAV-0, E-33, E-51, ART-CH) в геноме курицы исследовали в связи с композиционным составом (варьированием GC-содержания) генома хозяина. GC-богатые ретровирусы (ALV-родственные, ARTCH и EAV-0) локализованы, главным образом, в наиболее GC-богатых семействах изохор Н2, НЗ и Н4, GC-бедные HERV-I-родственные провирусы, Е-51 и Е-33 локализованы в GC-бедных семействах изохор LI, L2, а также в НІ (изопикничность). GC-богатый ретровирус EAV-HP, кроме ожидаемого наличия в GC-богатых изохорах, присутствует также в GC-бедных компартментах. Исследование экспрессии с помощью RT-PCR, а также анализ баз данных EST свидетельствуют о том, что экспрессия эндогенных ретровирусув курицы может быть тканеспецифичной. Это, в свою очередь, может влиять на картину провирусной локализации вследствие реинтеграции. Причиной изопикничной локализации эндогенных ретровирусов является композиционное соответствие между интегрированной последовательностью и хромосомным участком хозяина, что обеспечивает стабильность интеграции.